Extraction, characterization, antioxidant and antimicrobial activity of mango (Tommy Atkins) residues (Research, Society and Development, 2020)
Mango is a tropical fruit very well known and widespread, but almost half of its weight is discarded for being considered waste. Therefore this research aimed to characterize the flours of these residues (peel flour-PF, fiber flour-FF and kernel flour-KF), and prepare hydroalcoholic extracts (80%) of these flours in order to evaluate the antioxidant and antimicrobial capacity. For this purpose, the residues were separated, dried at 55ºC and ground to obtain the flour, and then the extracts were elaborated.PF was found to have the highest levels of vitamin C (179.98 mg/100 g) and minerals (2.62 % ash), whereas FF was higher in soluble solids (6.40 °Brix) and fibres (11.89 %) and KF was found to be rich in lipids (11.17 %). For bioactive compounds, KF showed higher levels of phenolic compounds (85.69 mg EAG g-1), followed by FF and PF (78.45 and 71.42 mg EAG g-1, respectively). KF extract had the highest antioxidant capacity for FRAP and ABTS (3139.90 µmol Fe(II)g-1 and 1370.23 µmol L-1 Trolox), respectively, followed by PF extract (2359.90 µmol Fe(II)g-1 and 406.90µmol L-1 Trolox) and FF extract (1129.90 µmol Fe(II)g-1 and 177.91µmol L-1 Trolox). The KF extract presented antimicrobial activity against Bacilus cereus, Escherichia coli and Salmonella Enteretidis, followed by PF extract (efficient for E. coli and Salmonella Enteretidis). It is possible to conclude that these flours can be used as a source of enrichment and their extracts can be used as a preservative to increase the food shelf life.